Analisis Miskonsepsi pada Mahasiswa Program Studi Matematika STKIP Harapan Bima - Juliawan, Rizcky; Putra, Berti Mandala (Jurnal Ilmiah Mandala Education (JIME), 2021)
Misconception Analysis in Mathematics Education Department Student of STKIP Harapan Bima. This research is a descriptive qualitative research that aims to explore misconceptions in students and students’ views about their misconceptions. The subject in this study were five students of Mathematics Department at STKIP Harapan Bima. Data collection techniques used in this study are tests and interviews. The test questions consist of geometry, probability theory, algebra, and calculus. Interviews were conducted to obtain information about students’ views on the their misconceptions. The result of the research shows that in every mathematics material, students experience misconceptions. Overall, misconceptions are most common in geometric materials, but they are not significantly different from other materials. The type of misconception that is most often experienced by students is confusion because the do not master the supporting cocepts. The misconception that is most rarely experienced by students is wrong classification of concept examples.